Social Networking Technology and Library and Information Science Profession: - (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The Library and its services have undergone tremendous changes from traditional to the present knowledge society driven by Information Technology. As well, the professional skill and competencies had also been dramatically changed to adapt with new technologies. The future of the library is governed by the new technological innovations in the areas of storage, retrieval, dissemination and management of information resources. The library profession can play a role to connect the people or users with the help of new technologies of social networking tools which have been applied with web technology and web 2.0 along with a number of technologies. These can transform Library Service and its profession more user friendly, social, better environments for retrieval, sharing and dissemination of information. This application of new technologies allows user to create, connect, covers, contribute use and share information. With the help of new technologies, the library profession could get closer to the users in creating social network that connect the users in different time and places. Hence this paper examines the applications of social media in the library services along with uses and its purposes.